The Role of Language in a Dynamic Situation of Globalization - Iskandarsyah Siregar (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2023)
The central and vital role and function of language make it very interesting to continue to be explored, questioned, and studied. The Republic of Indonesia has an official language used by its citizens, namely Indonesian. This language aims to unite the Indonesian nation, which is multicultural or has ethnic and cultural diversity, so that there is no distance separating fellow Indonesian citizens from hundreds of ethnic groups, according to the 1928 Youth Pledge Convention. What must be realized now is the use of Indonesian, which needs to be stronger. The weakness is not that it is not used at all but foreign terms that enter public discussion and tend to be considered more prestigious. This study uses a qualitative descriptive method that refers to literature sources and the results of previous studies. The existence of the Indonesian language can decline when most Indonesian people are happy and proud to use a foreign language considered more respectable and classier. However, the condition for the Indonesian language's existence is still in a safe stage. The Indonesian language can continue to exist by continuing to preserve it by adhering to the overall context and linguistic rules and developing its constructions by the needs and desires of civilization.